Evolução estrutural e termocronológica meso-cenozóica da Zona de Cisalhamento Portalegre, Nordeste do Brasil - Nóbrega, Mirnis Araújo da (2004)
The Portalegre shear zone (ZCPa), which is located in the Rio Grande do Norte and Paraíba states (Northeastern Brazil), is na important right-lateral, northeast-trending lineament formed during the Brazilian Orogenic Cicle). The ZCPa experienced na important brittle reactivation from the Mesozoic until the present. This reactivation led to the formation of the Gangorra, Pau dos Ferros, Coronel João Pessoa, Icozinho and Rio do Peixe basins. The reactivation northern parto f the ZCPa that marks the boundary of the Potiguar Basin is denominated Carnaubais Fault. Several fracture patterns were mapped along the ZCPa. Samples were collected in Neoproterozoic granite outcrops, along the ZCPa. These samples yielded AFT ages from 86±13 to 376±57 Ma, and the mean track length from 10.9±0.8 to 12.9±1.5 mm. Samples from the East block yielded mean ages of 103 Ma, mean track lengtn 12,1mm, and mean altitude 250m, whereas samples from West block yielded mean ages of 150 Ma, which reach 345 Ma and 220 Ma in the Pau dos Ferros and Coronel João Pessoa basins, respectively. Thermal history models were sorted out for each crustal block. Samples from West block recorded a thermal history from Carboniferous Period until the Permiano, when the block experienced gradual uplift until the Cretaceous, when it underwent downfaulting and heating until the Tertiary, and it eventually experienced a rapid uplift movement until recent times. Samples from the East block presented the same cooling and heating events, but at they occurred different times. The East block thermal record started ~140 Ma, when this block experienced cooling until ~75 Ma. Both blocks show a denundacion/erosional history more similar in the Tertiary. The AFT data indicate an important tectonic event ~140 Ma, when the West block experienced downfaulting and the East block experienced uplift. This tectonic process led to the generation of several sedimentary basins in the region, including the Potiguar basin. This tectonic event is also interpreted as a rift process caused by an E-W-trending extension. It the Tertiary, some heating events can be tentatively attributed to the macau volcanic event